MENINGKATKAN KONSERVASI ALAM MELALUI MATERI KEANEKARAGAMAN HAYATI DAN KEARIFAN LOKAL DI SEKOLAH - Marina Silalahi (Jurnal Dinamika Pendidikan, 2015)
Understanding the local heritage wisdom of Indonesia and biodiversity through the environmental education is a first step in conservation. This paper is based on a litera-ture review of scientific papers that have been published in books and scientific journals. The environmental education is an educational process that aims to create a community to have concern for the environment and matters related thereto. Formal education in schools is considered to be one of the effective ways to promote the conservation of biodiversity. Providing the material of the concept knowledge/ heritage wisdom and the concept of biodiversity in the formal curriculum in schools is expected to increase the awareness of the environment to preserve biodiversity. Biodiversity includes the diversity of habitats, species diversity, and genetic diversity. To preserve the environ-ment and the biodiversity local ethnic Indonesia has the local heritage wisdom and the knowledge taught to live in harmony with the environment and nature.Keywords : local heritage wisdom, biodiversity, environmental education, conservation